Nutritional variation in sorghum [Sorghum bicolor (L.) Moench] accessions from southern Africa revealed by protein and mineral composition. (September 2018) - Motlhaodi, Tiny; Bryngelsson, Tomas; Chite, Stephen; Fatih, Moneim; Ortiz, Rodomiro; Geleta, Mulatu
Abstract: Twenty-three sorghum accessions from five countries in southern Africa that were grown under two different environments in Botswana were analyzed for protein, calcium (Ca), iron (Fe), magnesium (Mg), manganese (Mn), phosphorus (P), potassium (K), sodium (Na) and zinc (Zn) concentrations. There were significant differences among the accessions for both protein and other nutrient contents. Broad-sense heritability (H 2 ) was overall high, ranging from 0.62 to 0.85, indicating the stability of the concentration of these nutrients in sorghum across environments. Low genotype by environment interactions (GxE) and high broad-sense heritability suggest that breeding for enhanced nutrient content may be feasible across environments. Accessions ZMB3947 and N406 may be a good source for both Fe and Zn since they recorded the highest value for both micronutrients. Among the macronutrients, accession S201 would be a good source of protein, Ca and P whereas accession ZIM1317 is a good choice as a Ca and K source. The genotypic variation in grain protein and mineral concentration revealed in this study is encouraging for selecting potential accessions for genetic improvement through breeding in Southern Africa. There were significant correlations among nutrients, which suggests that their concentration in sorghum landraces can be simultaneously improved. Highlights: Protein, Ca, Fe, K and Mg showed significant differences among sorghum accessions. A highly positive correlation was obtained between Mg and P in the sorghum grains. Genotype was the most important source of variation for almost all the nutrients. Broad-sense heritability (H 2 ) was overall high, ranging from 0.62 to 0.85. The Genotype by environment interactions (GxE) is generally low for the nutrients.